Thermal properties and shape memory behavior of titanium carbide reinforced poly (vinyl chloride)/poly (?-caprolactone) blend nanocomposites - Pekdemir, Mustafa Ersin (Taylor & Francis Inc, 2022)
PCL and PVC polymer blend was prepared and nanocomposites were obtained by doping TiC in various ratios. The characterization of the composites was studied using ATR-IR, TGA, DSC, SEM, and XRD. The results depicted that the TiC nanoparticles increased the thermal stability of the polymer blend. The DSC curves revealed that the T-g value of the polymer blend decreased as the TiC amount increased. The peaks of the XRD pattern are attributed to cubic TiC for polymer blend/TiC nanocomposites. The degree of crystallinity of the polymer blend was calculated as 21%, and in the case of nanocomposites, 25% and 30%.
Keywords: PCL; PVC blend; titanium carbide; nanocomposites; shape memory polymer; crystallinity